If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + 3y + -2 = 11y + -11 + -2y Reorder the terms: 15 + -2 + 3y = 11y + -11 + -2y Combine like terms: 15 + -2 = 13 13 + 3y = 11y + -11 + -2y Reorder the terms: 13 + 3y = -11 + 11y + -2y Combine like terms: 11y + -2y = 9y 13 + 3y = -11 + 9y Solving 13 + 3y = -11 + 9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9y' to each side of the equation. 13 + 3y + -9y = -11 + 9y + -9y Combine like terms: 3y + -9y = -6y 13 + -6y = -11 + 9y + -9y Combine like terms: 9y + -9y = 0 13 + -6y = -11 + 0 13 + -6y = -11 Add '-13' to each side of the equation. 13 + -13 + -6y = -11 + -13 Combine like terms: 13 + -13 = 0 0 + -6y = -11 + -13 -6y = -11 + -13 Combine like terms: -11 + -13 = -24 -6y = -24 Divide each side by '-6'. y = 4 Simplifying y = 4
| 128t-6t^2=112 | | 7+12x=1-6+x | | x*30=.30 | | x*30=30 | | X^2-6x=13 | | -64t+3t^2=56 | | 26600=.14*x | | 8+3x=80 | | -5(y+2)=-2(2y-2)+5y | | -9+q=-31 | | x^2+24x-27=0 | | n+8=0 | | -2(2y-3)+2y=8+2(3y-4) | | t+22.1=23.08 | | 6m-2*.5=m+12*.5 | | x-3(-4x+5)=2(x+1)+5(2x-1) | | 0=6t^2-128t+112 | | x+4=x^2-16x+60 | | 9+6(3c-1)= | | 1a+7=13a | | -2-7=-5+x | | 12y^2x^6-48k^4m^8= | | y^2x^6-48k^4m^8= | | 9(k-0.66)+33=0 | | 5x+6=-30-7 | | 183=x+2x+(x+15) | | b+5b-4*2b-3b-4= | | 128t-6t^2=0 | | 3x+56=9 | | x^6+x^2=0 | | 145=x+2x+(x-15) | | x^6+4*x^3+8*x^2+8*x+4=0 |